2D magnetic titanium carbide MXene for cancer theranostics. Issue 21 (18th May 2018) - Liu, Zhuang; Zhao, Menglong; Lin, Han; Dai, Chen; Ren, Caiyue; Zhang, Shengjian; Peng, Weijun; Chen, Yu
Abstract : A functionalized strategy for the construction of superparamagnetic 2D Ti3 C2 MXene nanocomposites was developed for highly efficient cancer theranostics. Abstract : Fast progress of two-dimensional (2D) materials has catalyzed the emergence of diverse new 2D nanosystems for versatile applications, among which 2D MXenes have attracted broad interest but their single functionality significantly restricts their extensive applications, especially in nanomedicine. Herein we report, for the first time, on the construction of superparamagnetic 2D Ti3 C2 MXenes for highly efficient cancer theranostics, which is based on the surface chemistry of specific MXenes for the in situ growth of superparamagnetic Fe3 O4 nanocrystals onto the surface of Ti3 C2 MXenes. These magnetic Ti3 C2 –IONPs MXene composites exhibit a high T 2 relaxivity of 394.2 mM −1 s −1 and efficient contrast-enhanced magnetic resonance imaging of tumors, providing the potential for therapeutic guidance. Importantly, these superparamagnetic MXenes have shown high photothermal conversion efficiency (48.6%) to guarantee the efficient photothermal killing of cancer cells and ablation of tumor tissues, which has been systematically demonstrated both in vitro and in vivo . The high biocompatibility of these elaborately designed magnetic Ti3 C2 -based MXene composites guarantees their further potential clinical translation. This report paves a new way for the functionalization of MXene-based 2D nanosheets for broadening their novel applications based on the unique surface chemistry of MXenes, especially in theranostic nanomedicine.